PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN HOTEL SEMAGI MUARA BUNGO - Fajar Ifan Dolly; Soleha Inka (Nusantara Hasana Journal, 2024)
The problems in this research include the lack of active interaction and reciprocal relationships between superiors and subordinates, such as inadequate training and guidance, providing encouragement and motivation to achieve goals. This is because there are no attractive rewards for employees. Another problem at the Semagi Hotel is that the working environment is not equipped with occupational health and safety (K3) standards for employees. The aim of this research is to determine the influence of motivation and work environment on the performance of Hotel Semagi Muara Bungo employees. This research uses quantitative research methods by distributing questionnaires and the data obtained will be processed using statistical calculations using multiple linear regression formulas. The collection technique used quota sampling with a sample size of 50 employees using a Likert scale as a measurement tool. High work motivation and an adequate and harmonious work environment can encourage employees to improve their performance. The results of this research indicate that there is a significant influence between work motivation and work environment on the performance of Hotel Semagi Muara Bungo employees. Based on the results of the f test, it is known that the significant effect of X1 and X2 simultaneously on Y is 0.001 < 0.05 and the calculated f value is 8.827 > 2.80. So it can be concluded that H3 is accepted, which means that there is a simultaneous influence of X1 and X2 simultaneously affects Y. Based on this, it can be concluded that there is a significant influence of work motivation and work environment together on the performance of Hotel Semagi Muara Bungo employees and it can be concluded that the third hypothesis is accepted.